Agronomical and Physiological Behavior of Spanish Hazelnut Selection “Negret-N9” Grafted on Non-suckering Rootstocks - Rovira, Mercè; Hermoso, J. Francisco; Rufat, Josep; Cristofori, Valerio; Silvestri, Cristian; Romero, Agustí (Frontiers in Plant Science, 2022)
‘Negret’ is the most widely planted hazelnut cultivar in Northeastern Spain, where it is highly appreciated by the local kernel marked for its favorable nut traits. Its main disadvantages are the high suckers’ emission, causing large maintenance costs every year and its medium-low vigor and susceptibility to iron chlorosis. In 2000, a trial to select new vigorous and non-suckering rootstocks for hazelnut was established at IRTA-Mas Bové (Spain). The ‘Negret N-9’ selection was grafted onto four clonal rootstocks (‘Dundee’ and ‘Newberg’ two selection of open pollinated C. colurna seedlings, the low suckering cultivar ‘Tonda Bianca’ and the local selection ‘IRTA MB-69’) and compared to the self-rooted ‘Negret N-9’ as control. The trial was designed as randomized complete block with 10 replications and one plant per plot (10 plants per treatment). Plant vigor, suckers’ emission, yield and nut and kernel traits have been evaluated over ten years (2003-2012). From the growing season 2006 to 2010, kernel qualitative traits as kernel skin color, oil contents in the kernel and their fatty acids profile were added to the characterization. Physiological data as steam water potential, stomatal conductance and leaf chlorophyll content were also evaluated during the growing season 2015. Results showed as clonal rootstocks had a strong influence on vigor and yield of ‘Negret N-9’. The ‘Dundee’, ‘Newberg’ and ‘IRTA MB-69’ rootstocks showed the highest vegetative growth and the lower suckers’ emission. Yield was highest in plants grafted on ‘Dundee’ rootstock. Referring to kernel qualitative traits, which are important for the hazelnut industry, rootstocks increased the oil stability and induced a brown light color in the kernel pellicle versus the brown dark color observed in nuts collected from self-rooted ‘Negret N-9’. Fatty acids profile was also influenced by grafting combination. Finally, physiological traits indicated higher overall performances for ‘Dundee’ rootstock, which was generally found to be the best rootstock for ‘Negret N-9’ in the experimental environment.